PURCHASE DECISION: PRODUCT STRATEGY, PRICE, PROMOTION AND DISTRIBUTION - Hendi Sobari; Samsudin (Nusantara Journal Of Management Business (NUMABI), 2023)
The purpose of this study was to determine the effect of product strategy, price, promotion and distribution on customer purchasing decisions for beverage products, Hydro Coco both partially and simultaneously in the city of Tasikmalaya. The object of research is the customer of Hydro Coco beverage products in the city of Tasikmalaya . The research method uses path analysis. Data collection was obtained through observation, questionnaires, and a literature study. Sampling using the Proportionate Stratified Random Sampling technique, the questionnaires distributed were 182 (one hundred and eighty-two) distributed in 7 (seven) Sports Gymnasiums in the city of Tasikmalaya. Based on the results of this study, it can be concluded that partially product strategy has no effect on purchasing decisions, prices, promotions, and distributions affect purchasing decisions, jointly product, price, promotion, and distribution have a significant effect on purchasing decisions.